Higher Levels of Alcohol Use Are Associated With Latent Tuberculosis Infection in Adults Living With Human Immunodeficiency Virus. (6th May 2020) - Puryear, Sarah B; Fatch, Robin; Beesiga, Brian; Kekibiina, Allen; Lodi, Sara; Marson, Kara; Emenyonu, Nneka I; Muyindike, Winnie R; Kwarisiima, Dalsone; Hahn, Judith A; Chamie, Gabriel
Abstract: We assessed associations between hazardous alcohol use and latent tuberculosis infection (LTBI) among adults living with human immunodeficiency virus (HIV) in Uganda. We compared tuberculin skin test positivity across medium, high, and very-high alcohol use levels, classified by AUDIT-C scores. In multivariable analysis, very high use was associated with LTBI (adjusted odds ratio 1.61, 95% confidence interval: 1.03–2.50).